1971
DOI: 10.1017/s1120962300011598
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Survey in 298 Normal Subjects and 1,253 Cases of Congenital Disorders during 1966-1970

Abstract: SummaryA survey of chromosomal abnormalities has been carried out in Italy since 1966. Among the 1,551 subjects examined, the following abnormalities were found: 2 cases of C/C translocation, 1 of D/C, 5 of D/D, and 9 of D/G; 2 cases of Patau's syndrome with D trisomy; 4 cases of Edwards' syndrome; 176 cases of Down's syndrome, of which 163 with regular trisomy, 4 with mosaicism, 7 with D/G translocation, 1 with G/G translocation, and 1 with C/G translocation; 10 cases with 47,XXY complement; 1 case with 46,XY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The structural change in the short arm of chromosome No. 17 has been interpreted by some authors as being due to satellites on this chromosome (Berg et al 1969, Daly 1970, Battaglia et al 1971), while others have considered it t o be a secondary constriction (Sandstrom & Jenkins 1973.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural change in the short arm of chromosome No. 17 has been interpreted by some authors as being due to satellites on this chromosome (Berg et al 1969, Daly 1970, Battaglia et al 1971), while others have considered it t o be a secondary constriction (Sandstrom & Jenkins 1973.…”
Section: Discussionmentioning
confidence: 99%
“…A marker chromosome 17p described by Sandstrom & Jenkins (1973 was considered from a similar point of view. However, some authors have demonstrated a relation between structural chromosome variant 17-18 and the occurrence of congenital malformations (Littlefield et al 1966, Daly 1970, Battaglia et al 1971).…”
mentioning
confidence: 99%
“…Such anomalies of the sex chromosomes, trisomy or partial monosomy for one member of a group of autosomes were described in different syndromes. Recent techniques make it possible to study chromosomes in various arrangements, in their balanced or unbalanced forms, and variations in the morphology of one homologue of a pair by comparison with the other (Battaglia et al, 1971). Friedreich's ataxia is usually inherited as an autosomal recessive.…”
Section: Introductionmentioning
confidence: 99%